2020
DOI: 10.1002/slct.201904965
|View full text |Cite
|
Sign up to set email alerts
|

Structure Optimization and Flame Barrier Performance Evaluation of Barrier Explosion‐Proof Materials Based on FLACS

Abstract: Blocking explosion-proof materials can quickly transfer heat, block flame propagation, and prevent explosion accidents. It has gradually become a rudimentary solution to the intrinsic safety of explosion or "secondary explosion" during the storage and transportation of flammable and explosive liquid or gaseous dangerous chemicals. The impact of the addition of explosion-proof porous materials in the storage tank on the shock wave was numerically simulated by FLACS and further analyzed with changes in pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The explosion venting experiment was carried out with an independently built experimental system. The experimental system was divided into four parts as shown in Figure 1: (1) large-diameter explosion pipeline experimental system [5 and 8]; (2) high-performance data acquisition system [1, 3, 4, and 6]; (3) explosion venting door [2]; and (4) ignition control system [7]. 2.1.…”
Section: Experiments Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The explosion venting experiment was carried out with an independently built experimental system. The experimental system was divided into four parts as shown in Figure 1: (1) large-diameter explosion pipeline experimental system [5 and 8]; (2) high-performance data acquisition system [1, 3, 4, and 6]; (3) explosion venting door [2]; and (4) ignition control system [7]. 2.1.…”
Section: Experiments Systemmentioning
confidence: 99%
“…At present, the existing explosion-proof devices in coal mines mainly include rock powder sheds, explosion-proof walls, explosion-proof water curtains, explosion-proof doors, and fire doors. For this reason, scholars have actively studied these technologies. Liu et al installed explosion venting doors of different qualities in the transparent glass cavity and found that the greater the quality of the explosion venting door, the longer it took to open the explosion venting door .…”
Section: Introductionmentioning
confidence: 99%